Pelatihan Pemanfaatan Limbah Jerami Sebagai Media untuk Budidaya Jamur Tiram Putih - Susilo; Meitiyani; Maryanti Setyaningsih (Jurnal Pemberdayaan Masyarakat, 2021)
Oyster mushroom cultivation (Pleurotus sp.) is relatively easy, because it has a fairly good adaptability to the environment and is very suitable to be developed in tropical regions such as Indonesia. One of the factors that play a major role is the planting medium which is generally in the form of wood powder. The supply of sawdust is decreasing, so that alternative media is needed which contains lots of organic matter and cellulose. Straw is an alternative substitute for wood powder media because it is abundant. The purpose of this activity was to provide skills in mushroom cultivation by utilizing straw waste to PKK women in Cigaragol village, Ciulengsi, Bogor. The skills about cultivating oyster mushrooms need to be disseminated to the wider community to overcome the shortage of supply of oyster mushrooms on the market. The method used in this activity is by lecturing, discussing and practicing. The results of training activities on the cultivation of white oyster mushrooms have increased community knowledge and skills by 71.9% which includes the introduction of 31.6% white oyster mushroom service, the benefits of white oyster mushrooms 52.6%, 100% white oyster mushroom habitat, 57.9% white wood powder media for cultivation of oyster mushrooms, straw media as an alternative to 100% white oyster mushroom cultivation and 89.5% white oyster mushroom cultivation technique. Training activities greatly help improve the knowledge and skills of cultivating white oyster mushrooms and potentially increase community income.